Analysis of Diospyrin: A Short Review - Das Sarma, Madhushree (Asian Journal of Chemistry, 2022)
Various analytical techniques are developed for detection, separation and quantification of a specific phytochemical or a component in a biological sample, particularly in relation to their therapeutic aspects. Diospyrin, a bis hydroxy naphthoquinonoid, is an important bioactive constituent of several Diospyros and Euclea spp. This compound has been identified as a prospective ‘lead molecule’ for novel chemotherapy for its significant in vivo and in vitro pharmacological activities. In this short review, some chromatographic and potentiometric methods of detection and quantitative estimation of diospyrin have been discussed.